Justice and beyond - Krishna Iyer, V. R. (New Delhi, 1982)
V.R. Krishna lyer, in this book expresses himself on a wide ranging variety of issues. Professionally, his subject is the Justice: of India and he exposes the weaknesses and proposes reforms so that the judicial process may truely become the delivery agent of social justice, He has gone beyond and written with zeal and amazing originality on a panorama of subjects. In this remarkable book, he has with refreshing fearlessness and passion for sociospiritual betterment explored men and matters, issues and themes, displaying a deep commitment to humanity and a critical approach to problems. 'Justice and Beyond' is a combination of stimulating scholasticism and sparkling style. It abounds with thought-provoking and penetrating presentation of views and ideas. It is a book for one who wishes his ideas to be jolted and refreshed and some new light infused into his mind.
Keywords: Law